(untitled) (Tempo e Argumento, 2023)
The holding of Second Vatican Ecumenical Council (1962-1965), with more than two hundred Brazilian bishops presents, changed the way of living the Christian faith in this country, however the dictatorial regime established in 1964, with institutional acts (A.I’s) and practices of political repression, interfered in this renewal process of Catholicism. This text analyzes the changes that occurred in the environment of the Archdiocese of Goiânia, central region of Brazil, which was under the staff of Dom Fernando Gomes dos Santos (1957-1985). The dimension of social justice was an important principle adopted in the process of receiving conciliar decisions, centrally inserted in the pastoral plans developed in the sixties of the twentieth century. This principle led the Catholic clergy to disagree with the simplistic anti-communism, propagated by authoritarian State, and, simultaneously, it was a platform for critique of capitalism.